Complete genome sequencing and analysis of Pasteurella multocida strain PMTB2.1 and expression of selected genes in iron-restricted environment - Jabeen, Shagufta (2017)
Pasteurella multocida (PM) is a Gram-negative, facultative anaerobic bacterium, belonging to the family Pasteurellaceae that commonly found as commensal in the upper respiratory tract of mammals and birds. However, P. multocida is often associated with acute as well as chronic infections in avian and bovine leading to significant morbidity and mortality, such as pasteurellosis and hemorrhagic septicemia (HS) in cattle and buffaloes. P.multocida subspecies multocida strain PMTB2.1 was first isolated from buffalos died of septicemia. The bacterium has been characterized based on biochemical tests and molecular identification based onPCR. Intrestingly, based on HS causing serogroup B-specific PCR (HSB-PCR), the isolate is not from serogroup B. Hence, an in depth genome wide analysis of PMTB2.1 was carried out. In this study, the genome of P. multocida strain PMTB2.1 was sequenced using third-generation sequencing technology, PacBio and analysed bioinformatically via de novo method followed by in depth characterization of the genome. In addition, expression of selected genes of PMTB2.1 grown in iron-restricted condition was also demonstrated based on real-time PCR study. Bioinformatics analysis based on de novo assembly of PacBio raw reads generated 3 supercontigs that were assembled to generate a draft genome with unresolved gaps regions. The gaps between the contigs in the assembled draft genome sequence were closed by PCR sequencing with primer walking strategy using Sanger sequencing. Start position of the circular genome of PMTB2.1 was set based on homology to reference genome P. multocida strain PM36950 and the circularity of the genome was confirmed by PCR. The complete genome sequence of P. multocida strain PMTB2.1 is composed of a single circular chromosome of 2,315,138 base pairs with 40.32 % GC content and a total of 2,176 potential genes. The genome was submitted to NCBI under the accession number, CP 007205.1. The annotated complete genome sequences of PMTB2.1 have 2,097 protein-coding sequences, 19 rRNA genes, 56 tRNA and 4 ncRNA genes. The genome also encode for more than 41 CDS (2%) that involved in iron regulation or iron uptake, 160 virulence genes and 12 antibiotic resistance genes including the complete Tad locus. The tad locus encodes 14 gene including several previously uncharacterized genes such as flp 2 that play important roles in the adhesion and colonization of the bacteria, biofilm formation as well as in pathogenesis of the disease. Multi-locus sequence typing against Rural Industries Research and Development Corporation (RIRDC) scheme indicated that PMTB2.1 matched to alleles from sequence type ST101. Comparative genome analysis showed that PMTB2.1 is closely related with other Pasteurella multocida strains with genomic distance less than 0.13. However, synteny analysis showed that genome structure of PMTB2.1 is more resembles to that of P. multocida serogroup A strain PM36950 as compared to that of P. multocida serogroup F strain PM70. However, PMTB2.1 genome lacks the Integrative Conjugative Element (ICE) of 86 kb that can only be detected in PM36950. Nevertheless, two intact prophage sequences of approximately 62 kb that were found in PMTB2.1, were absent in PM36950 and PM70. One of the phages is similar to transposable Mu like phage SfMu; however, the phage regions of PMTB2.1 were not associated with toxin-related genes, as detected in serogroup D toxigenic strain of P. multocida. Moreover, PMTB2.1 complete genome is approximately 34,380 kb smaller than PM36950 genome (2,349,518 bp), on the other hand approximately 15 kb specific region of PMTB2.1was absent in PM70 genome. The capsular sequence analysis of PMTB2.1 indicated that it is resembling the capsular sequence of P. multocida serogroup A with 99% sequence identity with A:1 capsular sequences. Furthermore, OrthoMCL analysis based on similarity among common genes showed that PMTB2.1 was clustered with bovine isolates and were separated from other P. multocida strains that infect avian and swine. Since P. multocida including PMTB2.1 has more than 2% of the genome encode for iron-regulated genes, the expression profiling of iron uptake genes namely fbpb, yfea, fece, fur and sialidase encoded by nana were characterized under iron-restricted environment where PMTB2.1 was grown in broth with and without iron chelating agent 2,2’ Bipyridine. Results of this study reflect that iron-reduced conditions have significant effect on the expression profiles of iron-regulating genes (p<0.05) and all of the four iron-related genes (fbpb, yfea, fece, fur) behave differently in response to iron reduction in media. The highest relative fold change (281.2 fold) of fece gene was observed at early, 30 minutes of treatment reveal that P. multocida may utilizes its periplasmic protein at early stage to acquire iron. Furthermore, down-regulation expression of fece from 4 to -1.5 with the elevated expression of other genes (fbpb and yfea) at later time points, 60 and 120 minutes suggest that PMTB2.1 control their iron requirements in response to iron availability by down regulating the expression of iron proteins. Moreover, the significant increase (p≤ 0.05) in fbpb expression (25 fold) at time point 60 and in Yfea expression (26 fold) at early time point 30 minutes with highest expression (42 fold) at 120 minutes reflect the utilization of multiple iron systems in P. multocida strain PMTB2.1. These results demonstrate the importance of iron in the survival of P. multocida. In conclusion, this study has provided insight on the genomic structure of PMTB2.1 in terms of potential genes that can functions as virulence factors and comparative pathogenomic information of valuable importance for future study in elucidating the mechanisms behind the ability of the bacterium in causing diseases in susceptible animals.